Pengawasan Pemerintah Daerah Terhadap Kerusakan Lingkungan Hidup - Wailissa, Syahril; Saptenno, Martinus Johanes; Holle, Eric Stenly (Jurnal Saniri, 2025)
In Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 23 of 2014 concerning Regional Government, it is emphasized that regional governments have an obligation to carry out supervision to prevent environmental damage. This study examines the case of weak regional government supervision of garnet sand mining activities in Negeri Haya, Central Maluku Regency, which caused coastal abrasion and damage to coastal ecosystems.The research method used is normative legal research with a legislative approach and a conceptual approach. The sources of legal materials consist of primary and secondary legal materials, with collection techniques through literature studies.Based on the results of the study, it was found that weak supervision of the Regional Government has a serious impact on the environment and community welfare, so that capacity building, strengthening of the supervisory function, and stricter law enforcement at the regional level are needed